Linguistic Recalls Of Ibn-Al Farus In His Book The Ahkam Al Quran Of On Ibn Attieya In His Book Al Moharer Al Wajez - Jabbar Ismail, Wafa; Shakir Mansoor, Ruqaya (Opción, 2019)
The present research aims to identify the biography of the two Imams Ibn al-Fars (d. 599 AH), Ibn ‘Atiyah (d. 542 AH) (may Allah have mercy on them). And com- paring the evidence of both Imams with the evidence of jurists in other schools of jurisprudence for the purpose of reaching the most correct words after presentation and discussion, includingthe recognition of the approach of the son of the Persians in the remediation, and highlight a great image of the keen interpreters to correct understanding of the words of God. That difference in the installation of the rules and assets of the science of interpretation.